Preliminary phytochemistry and antimicrobial activity of bark of Bauhinia racemosa Lamk. - Chavan, R T; Kadam, A S (Current Botany, 2012)
The bark of Bauhinia racemosa are reported to have great medicinal value. Phytochemical screening of the plant bark reveals the presence of carbohydrates, alkaloids, steroids and tannins. the methanol, ethanol, aqueous, acetone and petroleum ether extracts of bark of B. racemosa Lamk. prepared and antimicrobial activity were studied by agar well diffusion method against enteric bacterial pathogens such as E. coli, S. aureus, B. subtilis, P. aeruginosa and fungi A. niger and C.albicans. The methanol extracts had wide range of antimicrobial activity against enteric microbes than ethanol extracts, where as ethanol extract were slightly higher antibacterial activity than aqueous extract. Antimicrobial activity of various extracts of bark of B. racemosa was carried in attempt to develop a new pharmaceutical drug from natural origin for prevention of enteric infection.